2014
DOI: 10.3390/v6020782
|View full text |Cite
|
Sign up to set email alerts
|

HCMV Reprogramming of Infected Monocyte Survival and Differentiation: A Goldilocks Phenomenon

Abstract: The wide range of disease pathologies seen in multiple organ sites associated with human cytomegalovirus (HCMV) infection results from the systemic hematogenous dissemination of the virus, which is mediated predominately by infected monocytes. In addition to their role in viral spread, infected monocytes are also known to play a key role in viral latency and life-long persistence. However, in order to utilize infected monocytes for viral spread and persistence, HCMV must overcome a number of monocyte biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
125
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 99 publications
8
125
0
1
Order By: Relevance
“…We infected cells with HCMV (TB40/E) (24) and conducted time course experiments, extracting the nuclear fraction and performing PCR at each time point indicated. Consistent with previously reported data (21,22), we detected HCMV DNA in the nucleus of fibroblasts beginning at 30 min postinfection (mpi) (Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…We infected cells with HCMV (TB40/E) (24) and conducted time course experiments, extracting the nuclear fraction and performing PCR at each time point indicated. Consistent with previously reported data (21,22), we detected HCMV DNA in the nucleus of fibroblasts beginning at 30 min postinfection (mpi) (Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
“…In summary, we previously found that signaling initiated during HCMV binding to monocytes through EGFR and integrins triggers specific biological changes, such as enhanced survival (20) and accelerated differentiation (22), and now report that the signal derived from integrin engagement by gH/gL/UL128-131 plays a key role in HCMV nuclear translocation in infected monocytes. Our data suggest that this initial receptor-ligand engagement and the magnitude of the integrin signaling dictate the early entry steps, productive infection via appropriate trafficking, and degradation of the viral particle in late endosomes.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations